Inhibition by phospholipids of the interaction between R-ras, rho, and their GTPase-activating proteins. - Tsai, M H (1989)
Certain lipids were found to inhibit the interaction between rho and R-ras proteins and their respective GTPase-activating proteins (GAP). Inhibitory lipids were similar for each protein but differed significantly from those previously found to inhibit the interaction between ras protein and GAP activity. These data raise the possibility that ras and related proteins are controlled biologically by interactions between lipids and GAP molecules.